Optimization of the Safety Riding Program by the Education and Engineering Unit of the Bogor Police Traffic Unit to Reduce the Number of Traffic Violations among Private Employees (Indonesian Journal of Police Studies, 2024)
Two-wheeled traffic violations in the Bogor police jurisdiction are still an unresolved phenomenon to date, due to the increasing number of two-wheeled violations from year to year, especially among private employees, thus becoming the background in this study. The Bogor Police Traffic Unit Satyasa Unit has implemented a Safety Riding program for the community in the Bogor Regency area but Traffic violations still occur frequently, this can disrupt security, safety, order, and smooth traffic. So that in this study the authors are interested in describing the violations of two-wheeled traffic by private employees in the Bogor Police jurisdiction, Optimizing the Safety Riding program by the Bogor Police Traffic Satya Traffic Unit Unit to reduce the number of Traffic violations among private employees and the role and analyzing of factors who influenced him In analyzing, the author uses several theories and concepts including Management Theory, Communication Theory, Optimization Concept, Dikyasa Unit Concept, Traffic Unit Concept, Traffic Education Community Concept, Safety Riding Concept, and Traffic Violation Concept. By using a qualitative approach that is descriptive analytic, this is done in order to obtain the broadest picture of the problems that occur. The qualitative approach provides descriptive data in the form of words orally delivered by the primary source at the time of the interview, thus explaining the problem in depth. The results of the study found that: (1) Violation of two-wheeled traffic by private employees in the Bogor Police jurisdiction, the dominance of violations did not bring administrative completeness and did not use helmets; (2) the Safety Riding Program by the Bogor Police Traffic Satyasa Unit in order to reduce the number of Traffic violations among private employees in its implementation has not been able to arouse public awareness to implement Safety Riding; (3) Factors that influence the optimization of the Safety Riding program are human resources, funds / budget, materials / materials, methods of implementing facilities and infrastructure activities, and the community. From the results of the study the authors provide advice to the Bogor Police Traffic Satyasa Unit to increase the number of personnel in the implementation of the Safety Riding program. Suggestions for Dikyasa Unit personnel to improve their ability to attend training or Dikjur. As well as advice to the Bogor Police Traffic Police Satyasa Unit to adopt technology that supports the implementation of tasks and achieving goals such as smart helmets.
Keywords: Kata Kunci : Optimalisasi, Program Safety Riding, Mengurangi Pelanggaran Lalu Lintas.